Analisis Persiapan Implementasi Rekam Medis Elektronik Di Rumah Sakit Islam Siti Rahmah Padang - Dion Permadi; Annisa Wahyuni; Yuli Mardi; Nurul Fitri Khumaira (Iris Journal of Health Information Management, 2023)
Siti Rahmah Islamic Hospital, Padang is a type A private hospital located in Padang in preparation for implementing electronic medical records and also improving the quality of human resources and health services. This study aims to determine the preparation for implementing electronic medical records at RSI Siti Rahmah Padang. The research used was qualitative using interviews, the method of taking the subject of informants using purposive sampling with several informants 5 people and data collection using analysis techniques by interviewing informants. The results of the research that has been carried out to prepare for the implementation of electronic medical records at RSI Siti Rahmah Padang have been running from the start of the enactment of the PMK Law 24 of 2022 by increasing human resources through training on electronic medical records and providing facilities and infrastructure to support the successful implementation of medical records. electronic medical from the aspect of technology, and information technology (IT). From this research, it can be concluded that preparations for the implementation of electronic medical records have started with human resources increasing insight into medical record officers and medical staff in other healthcare facilities.